Interpretation of the Cu K-edge EXAFS spectra of Cu3N using ab initio molecular dynamics - Bocharov, Dmitry; Anspoks, Andris; Timoshenko, Janis; Kalinko, Aleksandr; Krack, Matthias; Kuzmin, Alexei (Elsevier Ltd, 2020)
Cubic copper nitride (Cu3N) has anti-perovskite structure, and its properties are strongly affected by anisotropic thermal vibrations of copper atoms. Ab initio molecular dynamics (AIMD) simulations were performed in the temperature range from 300 K to 700 K in order to probe the details of Cu3N lattice dynamics. The Cu K-edge extended X-ray absorption fine structure (EXAFS) spectrum of bulk Cu3N was used to validate AIMD simulations at 300 K. The AIMD results suggest strong anharmonicity of the Cu–N and Cu–Cu bonds, the rigidity of NCu6 octahedra and strong correlation in atomic motion within –N–Cu–N– atom chains as well as support anisotropy of copper thermal vibrations.
Financial support provided by ERDF project No. 1.1.1.2/VIAA/l/16/147 (1.1.1.2/16/I/001) under the activity “Post-doctoral research aid” realized at the Institute of Solid State Physics, University of Latvia is greatly acknowledged. This work was supported by a grant from the Swiss National Supercomputing Centre (CSCS) under the project ID s681 .
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Ab initio molecular dynamics; Copper nitride; Cu3N; Extended X-ray absorption fine structure (EXAFS)